Influence of repeated estrus synchronization treatment on hormone secretion, growth, and development of dairy goats - Sun, Shuang; Lv, Ming; Niu, Huimin; Luo, Jun (Frontiers in Veterinary Science, 2024)
This study investigated the effects of repeated pregnant mare serum gonadotropin (PMSG) and progesterone (P4)-mediated estrus synchronization (ES) treatment on the reproductive performance of dairy goats, and identified key metabolic and endocrine mechanisms influencing reproductive performance in does subjected to repeated ES treatments. Forty-eight Saanen does were randomly assigned to two groups (24 goats each) that received ES treatments either thrice fortnightly (3-PMSG) or once (1-PMSG) simultaneously with the third ES treatment of the 3-PMSG group during the breeding season. ES treatment was performed via the intravaginal insertion of a controlled internal drug release (CIDR) device impregnated with 300 mg P4, followed by 300 IU PMSG injections 48 h before CIDR withdrawal. Blood was collected to detect the level of hormones and blood biochemical indices. Additionally, estrus rate, fecundity rate, body weight, size, and lactation performance were measured. The results showed that repeated ES treatment markedly decreased the estrus rate and fecundity rate of goats. Among the does in all groups, there was no substantial difference in follicle stimulating hormone, luteinising hormone, gonadotropin-releasing hormone, melatonin, growth hormone, PMSG, total cholesterol, total protein, and glucose levels, as well as the body weight, body size, and lactation performance. Repeated ES treatment elevated estrogen (E2) levels 36, 48, and 72 h post-CIDR removal; increased P4 upon CIDR insertion; and raised PMSG antibody levels 24, 48, and 72 h post-CIDR removal. The results suggest that elevated anti-PMSG levels are the primary reason for the decline in ES efficiency, and that high E2 and P4 levels at some time points also impair reproductive performance. These findings provide novel insights into the metabolic effects of repeated PMSG stimulation in goats, guiding future reproductive hormone use in breeding practices.